2017
DOI: 10.1002/ccr3.937
|View full text |Cite
|
Sign up to set email alerts
|

“Chronic myelogenous leukemia in primary blast crisis” rather than “de novo BCRABL1‐positive acute myeloid leukemia”

Abstract: Key Clinical MessageDifferentiating chronic myelogenous leukemia in primary blast crisis (CML‐BC) from de novo BCR‐ABL1‐positive acute myeloid leukemia (AML) is a diagnostic challenge with therapeutic consequences. In our case, a basophilia, the presence of the Philadelphia chromosome in all metaphases and the strict exclusion of molecular hallmarks of AML lead us to retain the diagnosis of CML‐BC rather than BCR‐ABL1+ AML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…The t(9;22)/ BCR-ABL1 fusion leads to a permanently activated tyrosine kinase, which results in an unregulated cell division [2] . However, CML patients represent a distinct exception in this physiopathology in comparison to BCR-ABL1 positive AML patients: BCR-ABL1 fusion is the main driver event and sufficient to initiate the disease [21] . The overexpression of MECOM ( EVI1 ) in clonal evolution in CML patients leads to a BCR-ABL1 independent oncogenic pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The t(9;22)/ BCR-ABL1 fusion leads to a permanently activated tyrosine kinase, which results in an unregulated cell division [2] . However, CML patients represent a distinct exception in this physiopathology in comparison to BCR-ABL1 positive AML patients: BCR-ABL1 fusion is the main driver event and sufficient to initiate the disease [21] . The overexpression of MECOM ( EVI1 ) in clonal evolution in CML patients leads to a BCR-ABL1 independent oncogenic pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have also revealed that de novo AML with BCR/ABL1 has more prevalence of fusion protein 190 and NPM1 mutation in contrast to Ph+CML and also possess different treatment and prognostic value than CML with BCR/ABL1 in blast phase 8 . After a thorough literature search, we managed to execute a table to guide the CML‐BP and de novo gene AML,Table 2 5,6,8,9 …”
Section: Discussionmentioning
confidence: 99%
“…AML with BCR/ABL+ is considered to carry a worse prognosis, and hence its management approach is different from CML-BP [4]. There are overlapping clinical features between BCR-ABL + AML and myeloid CML blast crisis; moreover, there are no definite clinical criteria established yet to distinguish among these entities [4,5]. The involvement of molecular markers such as IKZF1, CDKN2A, and antigen receptor gene deletions in IGH or TRG2 can distinguish between de novo BCR-ABL + AML from myeloid blast crisis of CML [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of molecular markers such as IKZF1, CDKN2A, and antigen receptor gene deletions in IGH or TRG2 can distinguish between de novo BCR-ABL + AML from myeloid blast crisis of CML [1,2]. Certain other reported clinical features in the literature can also guide in this diagnostic dilemma, as mentioned in the table: 2; however, they may not be seen in every case [5,6].…”
Section: Discussionmentioning
confidence: 99%